Fractionated CO(2) Laser in the Treatment of Striae Alba in Darker Skinned Patients - A Prospective Study - Tehranchinia, Zohreh (Laser Application in Medical Sciences Research Center, 2018)

(untitled) (J Lasers Med Sci)
Introduction: In recent years, the positive effect of fractional CO(2) laser on increasing collagen fibers, and consequently its effect on treating striae has been suggested. The present study aims to assess the effectiveness of CO(2) fractional laser 10600-nm in the treatment of striae alba. Methods: In this prospective clinical trial, 2 treatment sessions of fractional CO(2) laser with 4-week interval was given to 30 patients with striae alba. Cutaneous resonance running time (CRRT) was measured at baseline and at week 4 and 3 months after the last session of laser therapy. The level of improvement was assessed by 2 independent dermatologists and patients after 3 months of follow up. Results: 16.7% of patients had moderate improvement, 63.3% had minimal improvement, and 20% had no improvement. A statistical significant difference was found in median CRRT during the study (P < 0.0001). The median CRRT levels were significantly higher in week 4 and 3 months after the last treatment compared to the baseline (both P < 0.001). Likewise, a significant increase was observed in median CRRT level from week 4 till the end of study (P < 0.001). Evaluation of participant satisfaction revealed that 10% were very satisfied, 10% satisfied, 3.3% slightly satisfied, and 76.7% unsatisfied. Conclusion: Striae alba remain a challenging condition to treat. The treatment of striae alba with CO(2) fractional laser results in minimal improvement with mild side effects.